(untitled) (TAJ: Journal of Teachers Association, 2009)
Leprosy is a chronic granulomatous multisystem disorder. Renal involvement is one of the dangerous complications of leprosy. Kidneys are usually involved during splanchnic localization of leprosy. The histopathological renal lesion spectrum includes spectrum of glomerulonephritis, renal amyloidosis and interstitial nephritis. Here we report a case of leprosy who presented with diffuse membranoproliferative glomerulonephritis with renal failure. doi: 10.3329/taj.v19i2.3157 TAJ 2006; 19(2): 84-86